Positive perception and efficacy of compression stockings for prevention of lower limb edema in pregnant women - Saliba-Júnior, Orlando Adas [UNESP]; Rollo, Hamilton Almeida [UNESP]; Saliba, Orlando [UNESP]; Sobreira, Marcone Lima [UNESP] (FapUNIFESP (SciELO), 2022)
Background: Pregnancy is characterized by physiological changes that can contribute to development of varicose veins, venous insufficiency, and leg edema. Objectives: To evaluate the effect of compression stocking on lower limb edema in pregnant women and their perceptions of wearing them. Methods: This was a randomized, controlled, prospective, parallel, blinded clinical trial conducted with 60 pregnant women randomly distributed into two groups: an intervention group (n = 30) wearing compression stockings and a control group (n = 30). Standardized ankle and calf measurements were taken of all 120 lower limbs using a tape measure. At the end of the study, a questionnaire was administered to identify perceived difficulties and advantages related to wearing compression stockings. Results: Pregnant women in the intervention group had a significantly smaller increase (p < 0.05) in calf and ankle diameters compared to those in the control group. The mean differences from the beginning to the end of gestation in the diameters of the right calf, left calf, right ankle, and left ankle respectively were 0.30 cm, 0.30 cm, 0.15, cm and 0.15 cm in the intervention group and 1.95 cm, 1.95 cm, 1.73 cm, and 1.87 cm in the control group. Most of the pregnant women had no difficulty wearing the compression stockings and all reported that they felt a difference in leg symptoms and would wear stockings again. Conclusions: Compression stockings were effective for preventing lower limb edema in pregnant women, who had a positive perception of wearing them.
Percepção positiva e eficácia das meias de compressão na prevenção de edema em membros inferiores de gestantes
Keywords: Controlled clinical trial; Edema; Pregnant women; Stockings, compression; Varicose veins